2021
DOI: 10.3389/fphar.2021.637273
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Key Role of NF-κB Signaling Pathway in the Treatment of Osteoarthritis With Bushen Zhuangjin Decoction, a Verification Based on Network Pharmacology Approach

Abstract: This study aimed to identify whether the NF-κB signaling pathway plays a key role in the treatment of osteoarthritis (OA) with Bushen Zhuangjin Decoction (BZD) based on a typical network pharmacology approach (NPA). Four sequential experiments were performed: 1) conventional high-performance liquid chromatography (HPLC), 2) preliminary observation of the therapeutic effects of BZD, 3) NPA using three OA-related gene expression profiles, and 4) verification of the key pathway identified by NPA. Only one HPLC-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Previous research has shown that the expression of MMP-9 is under the control of NF-κB signalling pathway ( Alves et al, 2014 ; Nambi, 2021 ). In our experiments, the MMP-9 levels were significantly increased after LPS exposure, consistent with our previous study ( Xu et al, 2021 ), but remarkably decreased after DHJSD treatment ( Xu et al, 2019 ). NF-κB p65 and IKK-β expressions were significantly upregulated after LPS exposure and downregulated after DHJSD or PDTC treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous research has shown that the expression of MMP-9 is under the control of NF-κB signalling pathway ( Alves et al, 2014 ; Nambi, 2021 ). In our experiments, the MMP-9 levels were significantly increased after LPS exposure, consistent with our previous study ( Xu et al, 2021 ), but remarkably decreased after DHJSD treatment ( Xu et al, 2019 ). NF-κB p65 and IKK-β expressions were significantly upregulated after LPS exposure and downregulated after DHJSD or PDTC treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Zhang et al found that virus-related, apoptotic, IL-17 and PI3K/Akt signalling pathway are involved in the mechanisms of Radix Achyranthis Bidentatae in treating acute OA using NPA ( Zhang et al, 2020 ), Huang et al used NPA and found that Simiao may exert its effect on multi-pathway such as IL-17 signalling pathway, HIF-1 signalling pathway, Toll-like receptor signalling pathway and TNF signalling pathway ( Huang et al, 2020 ). In our previous study, we also used NPA and OA in a cellular model and found that the NF-κB signalling pathway was the important inflammatory signalling pathway involved in the mechanism of Bushen Zhuangjin Decoction (BZD) in treating OA ( Xu et al, 2021 ). These studies had focused on investigating the potential molecular targets and mechanisms of a certain herbal formulation using NPA.…”
Section: Introductionmentioning
confidence: 99%
“…To further explore the biological processes involved in these differentially expressed proteins, Kyoto Encyclopedia of Genes and Genomes (KEGG) annotation analysis was performed for these proteins. 31 As shown in Fig. 6D and E, the major pathways involved in OA diseases belong to five categories, including metabolism, genetic information processing, environmental information processing, cellular processes, biological systems and human diseases.…”
Section: Resultsmentioning
confidence: 99%
“…6F shows the differences in the protein expressions of the three groups, indicating that BIIP could downregulate related proteins involved in the MAPK signaling pathway, such as dual specificity mitogen-activated protein kinase kinase 5 (Table S3†). Considering the previous research studies, the NF-κB, Wnt/β-catenin, and MAPK pathways were closely related to OA, 1,2,7,9,31 and the mRNA and protein levels of the related factors in these pathways were further studied in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical researchs have proven that BZD can e caciously relieve pain and improving the severity of osteoarthritis. The potential mechanism of BZD in improving KOA pain may be 1) inhibition of in ammation [9], 2) inhibition of chondrocyte apoptosis [10], 3) regulation of skeletal signaling pathways, and 4) regulation chondrocyte cycle regulation factors and improves chondrocyte vitality [11]. However, whether BZD affects the changes of brain functional activity, neurotransmitter transmission and pain in knee osteoarthritis has not been reported.…”
Section: Introductionmentioning
confidence: 99%